SOFTWARE FOR POWER CALCULATIONS: A COMPARATIVE STUDY - Marín Martínez, Fulgencio; Velandrino Nicolás, Antoino P.; Valera Espín, Antonio; Sánchez Meca, Julio (Anales de Psicología / Annals of Psychology)
Three statistical packages specifically designed for calculating statistical power are compared: STAT-POWER (Bavry, 1991), POWER (Borenstein & Cohen, 1988), and DESIGN (Dallal, 1988). The comparison criteria are interactivity, completeness, and accuracy. NOne of them does a better performance: STAT-POWER is the most complete, while POWER is teh most interactive, and can be used botho for research and for teaching. Finally, the potentials and limitations of each program are discused.